Investigation the polymorphism of gonadotropin releasing hormone receptor gene in Iraq sheep - Hasan AL-Mutar, Hayder Abdul-Kareem (The Iraqi Journal of Veterinary Medicine, 2017)
In the present study, the investigation includes the estrus activity after synchronization of estrus by using 20 mg impregnated sponges with Medroxy Progesterone Acetate for 12 days with 400 IU I/M injection of pregnant mare serum gonadotropin 24 hrs. before sponges withdrawal. All 30 Iraqi sheep’s showed (100%) estrus after sponge withdrawal. Twin percentage 40% while single percentage 60%. The polymorphisms of gonadotropin-releasing hormone receptor gene were analyzed as a genetic marker in 30 Iraqi sheep’s. Two noticed genotypes (GA and GT), and single nucleotide polymorphisms in the exon2 region of gonadotropin-releasing hormone receptor gene as genetic marker and correlated with high litter size after hormonal super ovulation response in sheep. The frequencies of alleles G,A and G,T in Iraqi ovine breeds were 0.50 and 0.50, respectively the outcomes revealed that GA, GT genotype was related with better litter-size in Iraqi ovine breeds. Therefore, these outcomes recommend that gonadotropin-releasing hormone receptor gene is a powerful candidate gene that impacts litter-size in sheep.